2011
DOI: 10.1007/jhep03(2011)126
|View full text |Cite
|
Sign up to set email alerts
|

On global flipped SU(5) GUTs in F-theory

Abstract: We construct an SU (4) spectral divisor and its factorization of types (3, 1) and (2, 2) based on the construction proposed in [1]. We calculate the chiral spectra of flipped SU (5) GUTs by using the spectral divisor construction. The results agree with those from the analysis of semi-local spectral covers. Our computations provide evidence for the validity of the spectral divisor construction and suggest that the standard heterotic chirality formulae are applicable to the case of F-theory on an elliptically f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 90 publications
1
33
0
Order By: Relevance
“…Here ι M 5,c : c F → M 5 is the embedding map, A M 5,c is a holomorphic connection on N c,F , and AR is a holomorphic connection on the bundle LR = Lr| M 5 24 . Our conjecture 24 We can define LR intrinsically on M 5 as follows. Start with the bundle O cF (R F ) where R F is the ramification divisor of the covering c F → D3.…”
Section: Mathematical Relationship To the M5-brane Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Here ι M 5,c : c F → M 5 is the embedding map, A M 5,c is a holomorphic connection on N c,F , and AR is a holomorphic connection on the bundle LR = Lr| M 5 24 . Our conjecture 24 We can define LR intrinsically on M 5 as follows. Start with the bundle O cF (R F ) where R F is the ramification divisor of the covering c F → D3.…”
Section: Mathematical Relationship To the M5-brane Theorymentioning
confidence: 99%
“…This approach to GUT model building uniquely combines two advantages of the heterotic and type II superstrings, giving rise to interesting GUT physics through the presence of exceptional gauge structures while localizing the gauge degrees of freedom in the internal space. In addition to many works on local model-building, there have been many attempts to construct global models [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] and properly understand chirality inducing G 4 -flux [29][30][31][32][33][34][35][36][37][38][39] and abelian symmetries [30,[40][41][42][43]. A proper understanding of chirality inducing flux and abelian symmetries is crucial for the understanding of instanton physics in the weakly coupled type IIb limit, and given the recent progress on these issues in F-theory one would hope to understand F-theoretic instantons in this light.…”
Section: Introductionmentioning
confidence: 99%
“…In [49] (and further in [53,54]) it is shown that when three-form fluxes are turned on in F-theory compactifications, rank-one fermion mass matrices receive corrections, leading to masses for lighter generations and CKM mixing. Flipped SU (5) [20,62,35,57,59,58], as well as some examples of SO(10) F-theory models [20,39,40] were also considered. Many of these models predict exotic states below the unification scale, and the renormalization group (RG) analysis of gauge coupling unification including the effect of such states and flux effects has been discussed in a series of papers [43]- [48,69].…”
Section: The Frameworkmentioning
confidence: 99%
“…In addition to enjoying [2,3] certain model-building advantages for grand unification over their heterotic and type II string counterparts, F-theory compactifications provide a broad view of the landscape; much of their strongly coupled physics can be understood in terms of the geometry of elliptically fibered Calabi-Yau varieties, which can be explicitly constructed and studied as a function of their moduli. Recent works have made significant progress in understanding the physics of F-theory compactifications, including globally consistent models [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], U (1) symmetries [20][21][22][23][24][25][26][27][27][28][29][30][31][32][33], instanton corrections [12,22,[34][35][36][37][38][39][40][41], the physics of codimension two and three singularities [42][43]…”
Section: Introductionmentioning
confidence: 99%